1992
DOI: 10.1002/app.1992.070440704
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of silane grafting and moisture crosslinking of polyethylene and ethylene propylene rubber

Abstract: SYNOPSISPeroxide initiated graft copolymerization of vinyl trimethoxy silane ( VTMO ) and vinyl triethoxy silane (VTEO) onto polyethylene ( P E ) and ethylene propylene copolymer ( E P R ) was studied. The kinetics of grafting, studied by differential scanning calorimetry, are the same for all the systems and the activation energy for VTMO is 170 ? 4 KJ/mol. Activation energy for VTEO is 185 ? 5 KJ/mol. The VTMO and VTEO graft copolymers of PE and EPR were prepared by reactive processing in a Brabender extrude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
1
4

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 9 publications
0
77
1
4
Order By: Relevance
“…Although the energy of the Si-O-Si linkages is high, 779 kJ/mol, the introduction of crosslinks hardly affect the polyethylene thermal stability, especially in a nitrogen atmosphere 21 . Similar results have been found by others researchers 12,15 .…”
Section: Thermal Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the energy of the Si-O-Si linkages is high, 779 kJ/mol, the introduction of crosslinks hardly affect the polyethylene thermal stability, especially in a nitrogen atmosphere 21 . Similar results have been found by others researchers 12,15 .…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…The crosslinking occurs through condensation reactions of these silanol groups, leading to the formation of siloxane bridges (-Si-O-Si-), which restricts the mobility of the polymeric chains. An organotin catalyst is generally employed [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] . This crosslinking process may be performed in one single step (Monosil process) or in two steps (Sioplas process) 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, na literatura científica poucos trabalhos são encontrados, sendo que a maior parte dos mesmos visa à obtenção de poliolefinas reticuladas [30][31] . Os polímeros obtidos têm sido explorados comercialmente como isoladores de cabos elétricos e de dutos para água quente [32,33] .…”
Section: Palavras-chave: Funcionalização De Polipropileno Vinilsilanunclassified
“…There is a further report in the literature [18] which focused on the film stability under chlorine treatment as a means to improve the stability of the LbL-assembled nanofilteration membranes in combined high ionic strength conditions and under chlorine treatment. In another approach, the stabilizing of the thin film is achieved by forming siloxane bonds owing to a silane coupling reaction between oppositely charged polyelectrolytes which leads to the crosslinking between the silane groups [18,19]. Egawa et al demonstrated [20] crosslinking between the sulfonate group in the polyanion and the diazonium ion in polycation due to exposure to UV light.…”
Section: Introductionmentioning
confidence: 99%